Conceptualizing Ambidextrous Leadership in Educational and Higher Education Organizations: A Qualitative Approach Based on Study Synthesis - Hedayatirad, Faezeh; Afkaneh, Soghra; Imani, Mohammad Naghi (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: This study aims to conceptualize ambidextrous leadership in educational and higher education organizations, exploring its impact on fostering creativity, innovation, and regional engagement.Methodology: The research employs a qualitative approach, conducting a systematic review of studies on ambidextrous leadership and synthesizing findings on the concept, characteristics, and specialized skills associated with ambidextrous leadership in universities. The review follows PRISMA guidelines, using databases such as Web of Science, SCOPUS, and Magiran to identify and analyze relevant literature.Findings: The study identifies ambidextrous leadership as encompassing three core areas: the concept of ambidextrous leadership, its specific characteristics in higher education, and the specialized skills necessary for university settings. Key aspects include balancing exploration and exploitation, flexibility, team collaboration, and macro-level management. Ambidextrous leadership supports universities in advancing regional socio-economic growth, promoting innovation, and adapting to dynamic conditions by encouraging both traditional academic functions and community-based roles.Conclusion: Ambidextrous leadership enables universities to simultaneously pursue diverse missions, balancing traditional academic roles with regional and entrepreneurial functions. This adaptability positions universities to meet modern socio-economic demands, enhancing their influence on local and global scales. However, implementing ambidextrous leadership requires substantial structural and managerial adaptation, highlighting a need for further empirical research on its application in academia.